Cardiovascular toxicities associated with immune checkpoint inhibitors: an observational, retrospective, pharmacovigilance study. Issue 12 (December 2018) - Salem, Joe-Elie; Manouchehri, Ali; Moey, Melissa; Lebrun-Vignes, Bénédicte; Bastarache, Lisa; Pariente, Antoine; Gobert, Aurélien; Spano, Jean-Philippe; Balko, Justin M; Bonaca, Marc P; Roden, Dan M; Johnson, Douglas B; et al.
Summary: Background: Immune checkpoint inhibitors (ICIs) have substantially improved clinical outcomes in multiple cancer types and are increasingly being used in early disease settings and in combinations of different immunotherapies. However, ICIs can also cause severe or fatal immune-related adverse-events (irAEs). We aimed to identify and characterise cardiovascular irAEs that are significantly associated with ICIs. Methods: In this observational, retrospective, pharmacovigilance study, we used VigiBase, WHO's global database of individual case safety reports, to compare cardiovascular adverse event reporting in patients who received ICIs (ICI subgroup) with this reporting in the full database. This study included all cardiovascular irAEs classified by group queries according to the Medical Dictionary for Regulatory Activities, between inception on Nov 14, 1967, and Jan 2, 2018. We evaluated the association between ICIs and cardiovascular adverse events using the reporting odds ratio (ROR) and the information component (IC). IC is an indicator value for disproportionate Bayesian reporting that compares observed and expected values to find associations between drugs and adverse events. IC025 is the lower end of the IC 95% credibility interval, and an IC025 value of more than zero is deemed significant. This study is registered withClinicalTrials.gov, numberNCT03387540 . Findings: We identified 31 321 adverse events reported in patients who received ICIs and 16 343 451 adverse events reported in patients treated with any drugs (full database) in VigiBase. Compared with the full database, ICI treatment was associated with higher reporting of myocarditis (5515 reports for the full database vs 122 for ICIs, ROR 11·21 [95% CI 9·36–13·43]; IC025 3·20), pericardial diseases (12 800 vs 95, 3·80 [3·08–4·62]; IC025 1·63), and vasculitis (33 289 vs 82, 1·56 [1·25–1·94]; IC025 0·03), including temporal arteritis (696 vs 18, 12·99 [8·12–20·77]; IC025 2·59) and polymyalgia rheumatica (1709 vs 16, 5·13 [3·13–8·40]; IC025 1·33). Pericardial diseases were reported more often in patients with lung cancer (49 [56%] of 87 patients), whereas myocarditis (42 [41%] of 103 patients) and vasculitis (42 [60%] of 70 patients) were more commonly reported in patients with melanoma (χ 2 test for overall subgroup comparison, p<0·0001). Vision was impaired in five (28%) of 18 patients with temporal arteritis. Cardiovascular irAEs were severe in the majority of cases (>80%), with death occurring in 61 (50%) of 122 myocarditis cases, 20 (21%) of 95 pericardial disease cases, and five (6%) of 82 vasculitis cases (χ 2 test for overall comparison between pericardial diseases, myocarditis, and vasculitis, p<0·0001). Interpretation: Treatment with ICIs can lead to severe and disabling inflammatory cardiovascular irAEs soon after commencement of therapy. In addition to life-threatening myocarditis, these toxicities include pericardial diseases and temporal arteritis with a risk of blindness. These events should be considered in patient care and in combination clinical trial designs (ie, combinations of different immunotherapies as well as immunotherapies and chemotherapy). Funding: The Cancer Institut Thématique Multi-Organisme of the French National Alliance for Life and Health Sciences (AVIESAN) Plan Cancer 2014–2019; US National Cancer Institute, National Institutes of Health; the James C. Bradford Jr. Melanoma Fund; and the Melanoma Research Foundation.